Next-generation bioinformatics: using many-core processor architecture to develop a web service for sequence alignment - Gálvez, Sergio; Díaz, David; Hernández, Pilar; Esteban, Francisco J.; Caballero, Juan A.; Dorado, Gabriel (Bioinformatics, 2010)
Motivation: Bioinformatics algorithms and computing power are the main bottlenecks for analyzing huge amount of data generated by the current technologies, such as the ‘next-generation’ sequencing methodologies. At the same time, most powerful microprocessors are based on many-core chips, yet most applications cannot exploit such power, requiring parallelized algorithms. As an example of next-generation bioinformatics, we have developed from scratch a new parallelization of the Needleman–Wunsch (NW) sequence alignment algorithm for the 64-core Tile64 microprocessor. The unprecedented performance it offers for a standalone personal computer (PC) is discussed, optimally aligning sequences up to 20 times faster than the non-parallelized version, thus saving valuable time. Availability: This algorithm is available as a free web service for the scientific community at http://www.sicuma.uma.es/multicore. The open source code is also available on such site. Contact: galvez@uma.es Supplementary information: Supplementary data are available at Bioinformatics online.